1997
DOI: 10.1097/00005768-199709000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective screening of 5,615 high school athletes for risk of sudden cardiac death

Abstract: Sudden cardiac death among high school athletes is a very infrequent though tragic occurrence. Despite widespread preparticipation screening for known causes of this event, the frequency has not changed. The ECG is an acknowledged sensitive screening tool for the common causes of sudden cardiac death in young athletes. The specificity of the ECG in this setting is believed to be relatively low in young athletes for which reason, in part, it is not used. We added an ECG to the usual preparticipation screening. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
1
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(102 citation statements)
references
References 28 publications
2
92
1
7
Order By: Relevance
“…The existing protocols ail include a medical history and a physical examination, in some cases diagnostic tests, of varying content. The persan performing the screening is also variable, some places allowing non-physicians [19,68,70,72,74,76,78,79,89,90] to conduct the examination, which decreases the chances of positive findings. One wonders what the results will be when technicians, nurses, chiropractors, or athletic trainers perform the cardiovascular screening.…”
Section: Discussionmentioning
confidence: 99%
“…The existing protocols ail include a medical history and a physical examination, in some cases diagnostic tests, of varying content. The persan performing the screening is also variable, some places allowing non-physicians [19,68,70,72,74,76,78,79,89,90] to conduct the examination, which decreases the chances of positive findings. One wonders what the results will be when technicians, nurses, chiropractors, or athletic trainers perform the cardiovascular screening.…”
Section: Discussionmentioning
confidence: 99%
“…В штате Невада (США) был проведен анализ ЭКГ у 5615 юных спор-тсменов, выявивший, что чувствительность этого ме-тода в идентификации серьезной кардиоваскулярной патологии составила 70% по сравнению с 3% при ис-пользовании только данных анамнеза и физикаль-ного осмотра [25]. Специфичность ЭКГ составила 97,4%, но только 0,4% (22 из 5615) детей были отве-дены от спортивных соревнований.…”
Section: обзоры литературыunclassified
“…50 Some US studies have suggested that ECG screening may be cost-effective on the basis of estimated cost per year of lives saved. 51,52 The 2007 AHA scientific statement/ screening guidelines 44 (coauthored by S.B. and M.J.A.)…”
Section: Ecg Screeningmentioning
confidence: 99%